The quality of life of sibling of children with attention deficit/hyperactivity disorder - Mariska Johana Heryputri; Laila Qodariah; Fredrick Dermawan Purba (University of Muhammadiyah Malang, 2022)
Siblings of children with ADHD have experiencing anxiety for various reason, including parents who focus more on caring for children with ADHD, experiencing pressure to take care of their siblings, and feeling concerned about their that had impact on their quality of life. The goal of this research was to get an overview of the quality of life of adolescents who have siblings with ADHD. 6 adolescents aged 13-17 years who have siblings with ADHD participated in this research. This study used the descriptive qualitative method. The data collection technique used semi-structured interviews using an interview guide created using The Interview Protocol Refinement Framework. Data collection was carried out during the COVID-19 pandemic so that interviews were conducted using the Google Meet and Zoom platform. The data analysis technique used thematic analysis. The results showed that there are 20 themes of four domains (physical, psychological, social, and environmental health) describe the quality of life in adolescents who have siblings with ADHD. Every adolescence’s quality of life domains is impacted by siblings with ADHD